High prevalence and plasmidome diversity of optrA-positive enterococci in a Shenzhen community, China - Fu, Yulin; Deng, Zhaoju; Shen, Yingbo; Wei, Weizhou; Xiang, Qiumei; Liu, Zhiyang; Hanf, Kunning; Huang, Suli; Lv, Zexun; Cao, Tingting; Peng, Changfeng; Zhang, Rong; et al. (Frontiers in Microbiology, 2024)
BackgroundThe emergence of optrA, which can confer resistance to phenicols and oxazolidinones in Enterococcus spp., poses a growing public health threat.Methods102 optrA-positive enterococci (OPEs) including various species were isolated from feces of 719 healthy volunteers in a Shenzhen community, China. Antimicrobial susceptibility of these isolates was tested. Whole-genome sequencing and bioinformatics analysis were performed to characterize molecular epidemiology of OPEs.ResultsCompared to optrA-negative enterococci (ONEs), antimicrobial resistance (linezolid, florfenicol, doxycycline, erythromycin and ciprofloxacin) and presence of antimicrobial resistance genes (ARGs) (fexA, cat, tet(M), erm(A), erm(B) and etc) were higher in OPEs. Phylogenetic analysis revealed that high similarly (19–338 SNPs) was observed between the optrA-positive E. faecalis from community and the strains from patients, animals, and environment. In 102 OPEs, the optrA gene was detected on the chromosome (n = 36), on plasmids (n = 62), or both (n = 4). A diverse range of optrA-carrying plasmid types was identified. The rep9-plasmid replicons were widely detected in E. faecalis (44/66), whereas repUS1-plasmid replicons were widely identified in other enterococcal species (7/66). Most of all ARGs harbored by isolates were co-existed on optrA-carrying plasmids, suggesting that the acquisition of optrA-carrying plasmids will pose a greater threat to public health. Notably, the pAD1 (rep9 family) + DOp1-type plasmids should receive more attention for the transfer of optrA given their high prevalence (36.36%), high number of co-located ARGs with optrA (83.87% of total ARGs) and presence in multiple sources. Tn6674, IS1216E, ISEnfa1 and ISEnfa5 are related to the transfer of chromosomal and plasmids-derived optrA, respectively. The bcrABDR gene cluster, fexA, and erm(A) were frequently identified surrounding optrA and may be transferred with optrA via IS1216E or ISEnfa1.ConclusionThe transfer of optrA gene is related to a variety of mobile elements (including plasmids, insertion sequences, transposons), which will promote the horizontal transfer of optrA. Moreover, many ARGs co-exist with optrA and could co-transfer with optrA. The acquisition of OPEs and optrA-carrying plasmids will pose a greater threat to public health and should be obtained more attention, especially optrA-positive E. faecalis and pAD1 + DOp1-type plasmids.